2021
DOI: 10.3390/molecules27010113
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Flavonoid Extraction from Xanthoceras sorbifolia Bunge Flowers, and the Antioxidant and Antibacterial Capacity of the Extract

Abstract: In the present work, the extraction process of total flavonoids (TFs) from X. sorbifolia flowers by ultrasound-assisted extraction was optimized under the response surface methodology (RSM) on the basis of single-factor experiments. The optimal extraction conditions were as follows: ethanol concentration of 80%, solid–liquid ratio of 1:37 (g/mL), temperature of 84 °C, and extraction time of 1 h. Under the optimized conditions, the extraction yield of the TFs was 3.956 ± 0.04%. The radical scavenging capacities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Based on the literature, it is said that almost all green plants contain flavonoid compounds. Flavonoid compounds have structural derivatives of 2-phenylchromone, most commonly found in plants with specific bioactivities such as preventing cell aging, helping the body's resistance to bacterial infections, and strengthening the body's immune system (Zhang et al 2021). This flavonoid activity correlates with Glutathione S-Transferase (GST) activity in human platelets, rat liver, and rat kidney tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature, it is said that almost all green plants contain flavonoid compounds. Flavonoid compounds have structural derivatives of 2-phenylchromone, most commonly found in plants with specific bioactivities such as preventing cell aging, helping the body's resistance to bacterial infections, and strengthening the body's immune system (Zhang et al 2021). This flavonoid activity correlates with Glutathione S-Transferase (GST) activity in human platelets, rat liver, and rat kidney tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Among these flavonoids, glabrol exerts a bactericidal effect by increasing the permeability of the cell membrane and collapsing the proton motive force. Zhang et al [ 159 ] also found that flavonoid extracts from Coriolus versicolors showed strong antibacterial activity against Escherichia coli , Staphylococcus aureus , and Bacillus subtilis in an experimental study. Yuan et al [ 160 ] revealed that the cell membrane is the main site of flavonoids acting on Gram-positive bacteria, which likely involves the damage to phospholipid bilayers, the inhibition of the respiratory chain, or the ATP synthesis.…”
Section: Pharmacological Properties Of Flavonoidsmentioning
confidence: 99%
“…X. sorbifolium possesses high stress resistance, cold resistance, drought resistance, barren resistance, and adaptability. It possesses edible, medicinal, ecological, energy, ornamental, and other properties [5][6][7][8], as well as significant development potential. Current X. sorbifolium research is mainly focused on successful cultivation and variety selection [9][10][11], pharmacological and therapeutic benefits of extracts [12], and extraction and utilization of seed kernel oil [13][14][15], all of which have shown relatively fruitful results.…”
Section: Introductionmentioning
confidence: 99%